PSYCHO-SOCIAL FACTORS AS CORRELATES OF SENIOR SECONDARY SCHOOL STUDENTS' ACHIEVEMENT IN ENGLISH READING COMPREHENSION IN IBADAN, NIGERIA (2023)
The study investigated self-efficacy, attitude and classroom interaction as correlates of senior secondary students' achievement in English reading comprehension in Ibadan, Oyo State. This study adopted the descriptive research design of correlational type. Ibadan South-West Local Government Area was purposively selected for having the largest number of public secondary schools in Ibadan. Random sampling technique was adopted to select ten (10) public senior secondary schools were randomly selected from Ibadan South- West Local Government Area. A total of300 Senior Secondary School II students were randomly selected 30 from each school. Four instruments were used for data collection: English Reading Comprehension Achievement Test (r=0.79), Questionnaire on Students self-efficacy (r =0.75), Questionnaire on Attitude to reading (r= 0.72) and Questionnaire on Student-Teacher Interaction (r=0.80). Data collected were analysed using descriptive statistics, Pearson Product Moment Correlation and multiple regression at 0.5 level of significance. The results indicated that students' achievement in reading comprehension had positive moderate correlation with students' self- efficacy (r=0.50), students' attitude to reading (r=.47) and student-teacher interaction (r=.42). The joint contribution of the independent variable (F(2.296)~85.19; Adj.R2 =0.18) was significant, accounting for 18.0% of the variance. Students' attitude to reading (f=0.33), students' self-efficacy (f}= 0.28), student- teacher interaction(j3=0.22) made a significant relative contribution to students' achievement. Based on the findings, it is recommended that teachers should take cognisance of these psychosocial factors to improve students' achievement in English reading comprehension.